Analysis of the evaluation performance of cadres care stunting in efforts to prevent stunting - Andi Salim; Irma Muslimin (Department of Nutrition at the Health Polytechnic of Aceh, Ministry of Health, 2023)
Stunting is a condition in which a child experiences growth disturbances so that the child's height is lower or shorter than the standard age. One of the efforts to prevent stunting is by providing assistance to pregnant women. Cadres as the spearhead of health workers who are near pregnant women and mothers with toddlers are expected to be able to monitor pregnant women and mothers with toddlers in efforts to prevent stunting. This study aims to analyze the evaluation of the performance of cadres in efforts to prevent stunting. The study used qualitative methods with in-depth interviews with four key informants and focus group discussions . In-depth interviews were conducted with 4 health cadres, and a Focus Group Discussion involving the Leaders of Organization of regional apparatus for family planning affairs , District Bappeda, Village Government, Health Center and Nutrition service staff. The data is then processed through the content analysis method. The data is then reduced through a coding process, summarized and drilled into partitions or sections that focus on questions. The results of the study show that, until now there has been no specific program in the context of efforts to prevent stunting to be carried out by cadres, even though there are currently various types of cadres besides health cadres who are known to be at posyandu, there are also other cadres who formed for the prevention of stunting, however, the implementation of the tasks has not been maximized because there is no specific program that is used as a reference in carrying out the tasks. In conclusion, that the performance of cadres is currently not optimal and focused on efforts to prevent stunting.